2019
DOI: 10.3746/pnf.2019.24.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Heshouwu (Polygonum multiflorum Thunb.) Extract Attenuates Bone Loss in Diabetic Mice

Abstract: This study investigated the effects and mechanism of Heshouwu (Polygonum multiflorum Thunb.) water extract (HSW) on diabetes-related bone loss in mice. HSW was orally administered (300 mg/kg body weight) to high-fat diet and streptozotocin-induced diabetic mice for 10 weeks. HSW significantly alleviated mouse body weight loss and hyperglycemia compared with the control group, and elevated serum levels of insulin, osteocalcin, and bone-alkaline phosphatase. HSW supplementation also significantly increased the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Active compound and related targets What was more, ranking the target degrees, 28 targets from the average degree (3.97) to the maximum degree (15) were listed in table 3. Protein-protein interaction network…”
Section: Resultsmentioning
confidence: 99%
“…Active compound and related targets What was more, ranking the target degrees, 28 targets from the average degree (3.97) to the maximum degree (15) were listed in table 3. Protein-protein interaction network…”
Section: Resultsmentioning
confidence: 99%
“…(PM), a classical herbal medicine, has been used for several centuries for its functions of hair-promoted, liver-tonifying and anti-aging [ 13 , 14 ]. Previous reports have shown that extracts of PM and its compounds had hypoglycemic effects [ 15 17 ]. However, researches on the hypoglycemic properties of PM are still limited and scarce.…”
Section: Introductionmentioning
confidence: 99%
“…(PM), a classical herbal medicine, has been used for several centuries for its functions of hair-promoted, liver-tonifying and anti-aging [13,14]. Previous reports have shown that extracts of PM and its compounds had hypoglycemic effects [15][16][17]. However, researches on the hypoglycemic properties of PM are still limited and scarce.…”
Section: Introductionmentioning
confidence: 99%
“…According to the degree of the compounds, the compounds from 2 times of the average degree(17.24) to the maximum degree(43) were screened out, namely resveratrol, apigenin, kaempferol, quercetin and luteolin, respectively, as shown in gure 2(b). What was more, ranking the target degrees, 28 targets from the average degree (3.97) to the maximum degree(15) were listed in table 3.…”
mentioning
confidence: 99%